ANALISIS EFISIENSI BANK UMUM PERSERO MENGGUNAKAN METODE DATA ENVELOPMENT ANALYSIS (DEA) - Ningsih, Diah Wuriah; Suripto, Suripto; Erfandi, Eli; Murdianingsih, Dian; Prayogi, Agung (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The purpose of this study is to analyze the efficiency of state-owned commercial banks and to analyze their development. Where efficiency is a parameter in measuring performance for banks. The Data Envelopment Analysis approach was used in this study with a quantitative method. Where there are two models used, namely the VRS (Variable Return to Scale) model and the CRS (Constant Return to Scale) model. State-owned commercial banks are the sample in this study for the period 2019 to 2022. Capital, Third Party Funds (DPK), and operational costs are used as variable inputs. Meanwhile, credit is used as a variable output. Based on the results of the analysis, it shows that based on the VRS model, the efficiency of state-owned commercial banks was obtained in almost all years except in 2019. Furthermore, the results of the analysis using the CRS model, several banks obtained efficiency results and several banks obtained inefficiency results. Even based on the average efficiency that existed during the study period, all of them experienced inefficiency, it's just that the efficiency value was at 0.9. The difference in the results of the two models used is because the VRS model overrides the production scale factor, while the resulting CRS model value is Overall Technical Efficiency.